Spirituality Nursing Among Patients with Schizophrenia - Sri Padma Sari; Diyan Yuli Wijayanti (Jurnal Ners, 2014)
Introduction: Spirituality has been reported to have benefits for recovery and quality of life for people with mental disorders including patients with schizophrenia. Spiritual can also be a coping strategy for patients with schizophrenia. This study aims to explore the importance of spirituality among patients with schizophrenia.Methods: This study uses descriptive phenomenological approach. There are 9 participants in this study, 7 participants are patients who diagnosed of schizophrenia and 2 participants are the caregivers. The data were analyzed by phenomenological hermeneutic approach.Results: Two main themes emerge from this study are 1) the meaning of spirituality is closed with Allah and the improvement of the spiritual practice and 2) the benefits of spirituality is recovery from the illness, symptoms management, behavioral change, emotional change and hope. Conclusion: Spirituality has an important role for patients with schizophrenia including helping the recovery process and hope. The results of this study are expected to give an overview of the spiritual need among patients with schizophrenia so that the nurses can give religion and or spiritual activity in the nursing intervention.